The Life Opportunities of Young Refugees: Understanding the Role, Function and Perceptions of Local Stakeholders - Zeynep Aydar (Social Sciences, 2022)
The focus on the local level in migration research became common when analyzing arrival contexts. Despite the relative autonomy of the local level and its crucial position in the multi-level migration governance, there is limited research on the role, function and perspectives of local stakeholders in Germany. This paper investigates the dynamics of local actors and aims at understanding their contribution to the life opportunities of young refugees. A post-industrial city, namely Dortmund, has been used as a case study for this explorative task. Building on 20 expert interviews conducted between November 2020 and September 2021, the results show that while the migration history of the city has positive influence on stakeholder perspectives, there are concrete horizontal discrepancies between governmental and non-governmental actors. Albeit being engaged with inclusive migration measures for decades, the governmental actors are found to be limiting youth’s chances, as they are bound to the legal framework of the national and federal levels. Contrarily, the non-governmental actors are of great importance as they challenge the system of burdens and actively create further possibilities for these youths. However, the article found that it is beyond the power of non-governmental actors to eliminate structural and legal barriers. The vertical and horizontal conflicts in multi-governance system are the major barriers for this. Nonetheless, local level actors appear critical in creating further opportunities and advocating for youth; therefore, their potential operational strength should not be undervalued.